Trust on Tradition/Customs of Batu Bara Community in the 19th Century - Muhammad Faishal; Syahrin Harahap; Amroeni Drajat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This article discussed the trust in the traditions / customs of Batu Bara people in the 19th century. Batu Bara is one of the regions in North Sumatera Province, Indonesia. In the 19th century Batu Bara communities were dominated by Malay ethnic groups and popularly referred to as "Malay Batu Bara". Malay Batu Bara had several traditions or customs that were considered important to be ritualized in everyday life. There were many traditions / customs in Batu Bara and in this study 3 traditions would be discussed namely; (1) Pantang larang, (2) Tapai Party, (3) Mandi Balimau. The approach used in this research was qualitative which produced descriptive data. In analyzing the data the researcher used data reduction, data presentation and drawing conclusions and verifies the data. The disciplinary approach in this research was socio-anthropological and based on historical values. From the data obtained, it was clear that there was trust in Batu Bara Community in the 19th century of the traditions / customs implemented in daily life.